MUD VOLCANOES AND SHEAR-WAVE IMAGING - AN EXAMPLE 4C TEST LINE IN THE CASPIAN SEA - Probert T.; Bryan R.; Ronen S.; Engelmark F.; Akenteiva E.; Browning G.; Rowson C.; Bakhshiev F.; Kawai N.; Nazarov A. (My University, 2001)
The general description of a mud volcano is an injection or eruption of mud fluids from a highly pressurized zone to a shallower, lower-pressure zone or eruption to the surface. These features are often associated with gas and fluidized sediments forming complex structures. They are poorly resolved using conventional P-wave seismic imaging and they present a number of challenges for hydrocarbon exploration and development. The benefits from converted-wave methods include imaging through the gas, improved resolution, pore-pressure prediction, and better imaging of complex structures with wide-azimuth geometry.